2020
DOI: 10.1096/fj.202001711r
|View full text |Cite
|
Sign up to set email alerts
|

The interaction partners of (pro)renin receptor in the distal nephron

Abstract: The (pro)renin receptor (PRR), a key regulator of intrarenal renin-angiotensin system (RAS), is predominantly presented in podocytes, proximal tubules, distal convoluted tubules, and the apical membrane of collecting duct A-type intercalated cells, and plays a crucial role in hypertension, cardiovascular disease, kidney disease, and fluid homeostasis. In addition to its well-known renin-regulatory function, increasing evidence suggests PRR can also act in a variety of intracellular signaling cascades independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 159 publications
(406 reference statements)
0
14
0
Order By: Relevance
“…The kidney has a fundamental role in the renin-angiotensin system (RAS), which regulates blood pressure, salt retention, and fluid balance [32][33][34]. In the classical system, renin cleaves angiotensinogen to form angiotensin I (AngI), which is subsequently converted to AngII by angiotensin-I converting enzyme (ACE).…”
Section: Interaction Of the As With The Renin-angiotensin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The kidney has a fundamental role in the renin-angiotensin system (RAS), which regulates blood pressure, salt retention, and fluid balance [32][33][34]. In the classical system, renin cleaves angiotensinogen to form angiotensin I (AngI), which is subsequently converted to AngII by angiotensin-I converting enzyme (ACE).…”
Section: Interaction Of the As With The Renin-angiotensin Systemmentioning
confidence: 99%
“…Intravenous (IV) apela-32 administration to salt-loaded salt-sensitive Dahl rats decreases medullary PRR and renin levels, urinary soluble PRR, renin, angiotensinogen and AngII excretion, blood pressure and kidney injury. It has been suggested that the apelinergic ligands antagonize renal PRR expression and RAS activation through cAMP-dependent but AR-independent signaling in the CD [34].…”
Section: Interaction Of the As With The Renin-angiotensin Systemmentioning
confidence: 99%
“…Given previous reports that megalin‐mediated endocytosis of renin and prorenin requires PRR, 4–6 Saigo et al have stated the close physiological relationship between PRR and renin/prorenin that intracellular alternative renin but not conventional renin/prorenin may be involved in PRR signaling 3 . This may challenge the idea that PRR is directly involved in multiple intracellular signaling cascades, including mitogen‐activated protein kinase (MAPK) signaling, wnt/β‐catenin signaling, cyclooxygenase‐2/prostaglandin E 2 signaling, and the apelinergic system 2,7 . Additionally, PRR also works as an accessory subunit of the vacuolar H + ‐ATPase (V‐ATPase) that regulates acid‐base homeostasis, cell survival, and urine acidification 7 …”
Section: Introductionmentioning
confidence: 99%
“…This may challenge the idea that PRR is directly involved in multiple intracellular signaling cascades, including mitogen‐activated protein kinase (MAPK) signaling, wnt/β‐catenin signaling, cyclooxygenase‐2/prostaglandin E 2 signaling, and the apelinergic system 2,7 . Additionally, PRR also works as an accessory subunit of the vacuolar H + ‐ATPase (V‐ATPase) that regulates acid‐base homeostasis, cell survival, and urine acidification 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation